2008
DOI: 10.2172/943932
|View full text |Cite
|
Sign up to set email alerts
|

Active load control techniques for wind turbines.

Abstract: This report provides an overview on the current state of wind turbine control and introduces a number of active techniques that could be potentially used for control of wind turbine blades. The focus is on research regarding active flow control (AFC) as it applies to wind turbine performance and loads. The techniques and concepts described here are often described as "smart structures" or "smart rotor control". This field is rapidly growing and there are numerous concepts currently being investigated around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 115 publications
0
28
0
Order By: Relevance
“…Pechlivanoglou and Eisele [9] investigated the operation of plasma actuators on wind turbine airfoils at a wide range of Reynolds numbers and found that the effect of all the investigated plasma actuators vanished at Re > 10 5 . The energy conversion efficiency is also another operational parameter which highly depends on the actuators design, and undergoes further investigation.…”
Section: Plasma Control Devicementioning
confidence: 99%
See 2 more Smart Citations
“…Pechlivanoglou and Eisele [9] investigated the operation of plasma actuators on wind turbine airfoils at a wide range of Reynolds numbers and found that the effect of all the investigated plasma actuators vanished at Re > 10 5 . The energy conversion efficiency is also another operational parameter which highly depends on the actuators design, and undergoes further investigation.…”
Section: Plasma Control Devicementioning
confidence: 99%
“…Pechlivanoglou and Eisele [9] investigated the operation of plasma actuators on wind turbine airfoils at a wide range of Reynolds numbers and found that the effect of all the investigated plasma actuators vanished at Re > 10…”
Section: Plasma Control Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Wind turbine blade lift control mechanisms that ultimately control power capture have included pitch variation or feathering, trailing edge flaps, vortex-generators, and even plasma systems [3] [4] [7] [8] [9] [10]. During rotation of a VAWT, each blade experiences different flow conditions requiring individual control for maximum efficiency [11].…”
Section: Circulation Controlmentioning
confidence: 99%
“…As a consequence of the boundary layer separation, the air flow on the blade is detached leading to increased aerodynamic losses and noise generation (Wagner et al 2012). In order to reduce the flow separation, different flow control devices have been developed and implemented on the blades during the last few decades (Van Dam et al 2008). Several flow control devices, such as trailing edge flaps, microtabs, microflaps, plasma actuators, active flexible walls or vortex generators, have been proposed in literature (Van Dam et al 2007Andersen et al 2010;Johnson et al 2010;Nelson et al 2008;Gao et al 2015).…”
Section: Introductionmentioning
confidence: 99%